(untitled) (British Journal of Multidisciplinary and Advanced Studies, 2023)
Dyspnea is frequently complained for several weeks in Long-COVID, still being its underlying pathophysiology poorly investigated in the clinical setting. Aim: to investigate the lung functional pattern of Long-COVID patients and healthy controls (HC). Non-smokers aged ≥18years, discharged after COVID pneumonia were investigated, were classified as low dyspnea scorers (LDS) or high dyspnea scorers (HDS) if they were not complaining or otherwise still complaining dyspnea 12-16 weeks after discharge. A group of non-smoking HC was compared. Spirometric parameters; usual DLCO; simultaneous single-breath DLNO (sDLNO) and DLCO (sDLCO); lung capillary blood volume (Vc), and expiratory nitric oxide (eNO) were assessed. Their linear association was explored by correlation analysis. Area under the curve (AUC) were used to determine the best predictors of being HC, LDS or HDS, and to establish optimal cut-off values. 40 Long-COVID patients (19 LDS; 21 HDS) and 28 HC were investigated. FEV1, VC and FEV1/VC were equal in LSD and HSD. A decreasing trend (p<0.0001) for DLCO, sDLCO, sDLNO and Vc, and a corresponding increasing trend (p<0.0001) for sDLNO/sDLCO and eNO were detected from HC to HDS patients. sDLNO/sDLCO and Vc resulted the best predictors of belonging to the HDS group. Optimal cut-off values were 113.5 for sDLNO/sDLCO ratio and 58.5 for Vc, respectively. Data suggest the reduction of lung capillary blood volume as the main disorder in these cases and contribute to phenotyping respiratory troubles in Long-COVID. These disorders would be otherwise neglected by usual lung function parameters, due their low specificity.